Wastewater : From Waste to Resource – The Case of Arequipa, Peru - World Bank (World Bank, Washington, DC, 2019)
SEDAPAR S.A. (Servicio de Aqua Potable y Alcantarillado de Arequipa) is one of the public service enterprises in Peru. It is a limited liability company owned by 8 provincial municipalities and 26 district municipalities in Arequipa Department. It provides water and sanitation services to the metropolitan area of Arequipa and a large part of the department. SEDAPAR serves over 1.1 million inhabitants through 280,000 connections. Coverage ratios are over 94 percent for water and over 80 percent for sanitation services. SEDAPAR is the second-largest utility in Peru in terms of population served—after Sedapal in Lima—and is the largest in terms of coverage area. Arequipa Department, at a size of 63,345 square kilometers (k